SIRT1 inhibits EV71 genome replication and RNA translation by interfering with the viral polymerase and 5′UTR RNA - Han, Yang (J Cell Sci, 2016)
Enterovirus 71 (EV71) possesses a single-stranded positive RNA genome that contains a single open reading frame (ORF) flanked by a 5′ untranslated region (5′UTR) and a polyadenylated 3′UTR. Here, we demonstrated that EV71 activates the production of silent mating type information regulation 2 homolog 1 (SIRT1), a histone deacetylase (HDAC). EV71 further stimulates SIRT1 sumoylation and deacetylase activity, and enhances SIRT1 translocation from the nucleus to the cytoplasm. More interestingly, activated SIRT1 subsequently binds with the EV71 3D(pol) protein (a viral RNA-dependent RNA polymerase, RdRp) to repress the acetylation and RdRp activity of 3D(pol), resulting in the attenuation of viral genome replication. Moreover, SIRT1 interacts with the cloverleaf structure of the EV71 RNA 5′UTR to inhibit viral RNA transcription, and binds to the internal ribosome entry site (IRES) of the EV71 5′UTR to attenuate viral RNA translation. Thus, EV71 stimulates SIRT1 production and activity, which in turn represses EV71 genome replication by inhibiting viral polymerase, and attenuates EV71 RNA transcription and translation by interfering with viral RNA. These results uncover a new function of SIRT1 and reveal a new mechanism underlying the regulation of EV71 replication.